MAKING NATURAL PRODUCTS RESEARCH EXCITING AND PURPOSEFUL IN AFRICA - Abegaz, B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Natural products research has by-and-large been a South-North collaboration with the African contribution often reduced to either supplying the plant material or being confined to the rudimentary aspects of the research. The remaining, exciting part usually came from the Northern counterpart. Many of the international funding agencies, including the official bilateral and multilateral cooperation agreements started and maintained the forgoing status quo. Such framework for natural product research did not enhance the capacity building efforts in Africa. Thankfully this has been changing over the last decade as African scientists found new ways of cooperation among themselves and because a number of institutions began to realize the need to invest in major scientific equipment and other research facilities. This presentation will highlight the joint efforts of phytochemists, biochemists and synthetic organic chemists from various institutions in Africa to do exciting, and development-oriented research in natural products. Results of a broad screening of 200 plants using the screens-to-nature bioevaluation technologies will be presented. We will also present the most recent results revealing novel natural products from medicinal plants used in Botswana and Cameroon. These include a number of novel triterpenes from Cameroonian Dubosia species, novel phenolic compounds from Morus spp. and compounds that have the potential to potentiate chloroquine in malaria therapy